Eco-friendly core material with excellent biodegradability and drain board using the core material

KR103036126B1Active Publication Date: 2026-10-21DAEHAN I M
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250212716
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-12-29
Publication Date
2026-10-21
Estimated Expiration
2045-12-29
Patent Text Reader

Abstract

The present invention relates to an eco-friendly drain board core material with excellent biodegradability and a drain board to which the core material is applied. More specifically, the drain board core material comprises a biodegradable composition with improved flexibility and biodegradation rate due to controlled crystallinity, wherein the biodegradable composition comprises plant-derived or petroleum-based 1,4-butanediol, succinic acid, bishydroxybutylene adipate-succinate-terephthalate oligomer, a catalyst, and a stabilizer. The drain board core material made of the above components and the drain board to which the core material is applied exhibit excellent flexibility because it contains a long-chain oligomer with a weight-average molecular weight of 800 to 2000 g / mol to control the crystallinity of polybutylene succinate, and exhibit excellent processability and biodegradability due to the application of a biodegradable composition with an improved biodegradation rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an eco-friendly drain board core material with excellent biodegradability and a drain board to which the core material is applied. More specifically, the invention relates to an eco-friendly drain board core material with excellent processability and biodegradability and a drain board to which the core material is applied, wherein a biodegradable composition is applied that includes a long-chain structured oligomer with a weight-average molecular weight of 800 to 2000 g / mol to control the crystallinity of polybutylene succinate, thereby exhibiting excellent flexibility and improved biodegradation rate. Background Technology

[0002] Generally, drain boards are widely used in soft ground improvement, road and railway foundation construction, retaining walls and landfill structures, etc., for the purpose of rapidly draining pore water or seepage water within the ground to promote ground consolidation and ensure structural stability. Such drain boards typically consist of a core material with multiple moisture channels formed therein and a filter material that surrounds the core material to prevent soil inflow.

[0003] Conventional drain board core materials have primarily been manufactured using petroleum-based synthetic resins such as polypropylene (PP) and polyethylene (PE). While these materials offer the advantages of excellent mechanical strength and processability, they pose a problem of causing soil and environmental pollution because they undergo almost no natural decomposition during landfilling or disposal after use. In particular, drain boards used in large-scale civil engineering projects are used in very large quantities, and their long-term persistence after construction is completed is cited as a factor that exacerbates the environmental burden.

[0004] To address the aforementioned problems, recent attempts have been made to apply biodegradable resins, such as polylactic acid (PLA) and polybutylene succinate (PBS), as core materials for drain boards. However, these biodegradable resins generally have high crystallinity and limited molecular chain mobility, making it difficult to secure sufficient flexibility and leading to issues such as breakage or cracking during processing. In particular, since drain board core materials are subjected to repeated bending and external forces during molding and installation, a lack of material flexibility results in reduced workability and decreased product reliability.

[0005] Furthermore, core materials utilizing conventional biodegradable resins often have a relatively slow biodegradation rate or frequently sacrifice biodegradability to prevent a decline in mechanical properties, which limits their ability to simultaneously satisfy eco-friendliness and practical performance. For example, if low-molecular-weight components are excessively included to enhance biodegradability, problems such as a rapid decline in product strength and durability may occur.

[0006] Therefore, there is a need to develop eco-friendly materials that can secure the mechanical strength and flexibility required for drain board core materials while simultaneously allowing for smooth biodegradation in the natural environment after use. Prior art literature

[0007] Korean Registered Patent No. 10-1754930 (Published July 7, 2017) Korean Registered Patent No. 10-2403019 (Published May 26, 2022) The problem to be solved

[0008] The objective of the present invention is to provide an eco-friendly drain board core material with excellent processability and biodegradability, and a drain board to which the core material is applied, by applying a biodegradable composition that exhibits excellent flexibility and improved biodegradation rate by controlling the crystallinity of polybutylene succinate by including a long-chain structured oligomer with a weight-average molecular weight of 800 to 2000 g / mol. means of solving the problem

[0009] The objective of the present invention can be achieved by providing an eco-friendly drain board core material with excellent biodegradability, comprising a biodegradable composition with improved flexibility and biodegradation rate due to controlled crystallinity, wherein the biodegradable composition comprises plant-derived or petroleum-based 1,4-butanediol, succinic acid, bishydroxybutylene adipate-succinate-terephthalate oligomer, a catalyst, and a stabilizer.

[0010] According to a preferred feature of the present invention, the biodegradable composition is prepared by mixing 100 parts by weight of plant-derived or petroleum-based 1,4-butanediol, 120 to 140 parts by weight of succinic acid, 12 to 18 parts by weight of bishydroxybutylene adipate-succinate-terephthalate oligomer, 0.1 to 0.2 parts by weight of catalyst, and 0.1 to 0.2 parts by weight of stabilizer, carrying out an esterification reaction, and then carrying out a polycondensation reaction.

[0011] According to a preferred feature of the present invention, the bishydroxybutylene adipate-succinate-terephthalate oligomer comprises 35 to 45 parts by weight of succinic acid, 45 to 55 parts by weight of adipic acid, and 80 to 90 parts by weight of dimethyl terephthalate in 100 parts by weight of 1,4-butanediol. , It is prepared by mixing 0.05 to 0.1 parts by weight of tetrabutyl titanate and 0.1 to 0.2 parts by weight of trimethyl phosphate and carrying out an esterification reaction.

[0012] According to a preferred feature of the present invention, the catalyst comprises tetrabutyl titanate and dibutyltin oxide in a weight ratio of 1:1.

[0013] According to a preferred feature of the present invention, the stabilizer comprises trimethylphosphate.

[0014] According to a preferred feature of the present invention, the esterification reaction is carried out at a temperature of 200 to 220°C for 120 to 200 minutes.

[0015] According to a preferred feature of the present invention, the polycondensation reaction is carried out for 150 to 200 minutes at a temperature of 240 to 250°C and a reduced pressure of 1.5 Torr or less.

[0017] In addition, the objective of the present invention can also be achieved by providing an eco-friendly drain board with excellent biodegradability, comprising a core material made of the above-mentioned core material for an eco-friendly drain board with excellent biodegradability and a filter material surrounding the core material, wherein the core material has a plurality of drainage channels formed therein and the filter material is formed of a polylactic acid fiber material. Effects of the invention

[0018] The eco-friendly drain board core material with excellent biodegradability according to the present invention and the drain board to which the core material is applied exhibit excellent flexibility and a biodegradable composition with improved biodegradation rate by including a long-chain structured oligomer with a weight-average molecular weight of 800 to 2000 g / mol to control the crystallinity of polybutylene succinate, thereby providing an excellent effect of providing an eco-friendly drain board core material with excellent processability and biodegradability and a drain board to which the core material is applied. Specific details for implementing the invention

[0019] Hereinafter, preferred embodiments of the present invention and the physical properties of each component are described in detail. This description is intended to be sufficient for a person skilled in the art to easily practice the invention, and does not imply that the technical scope and concept of the present invention are limited thereby.

[0021] The eco-friendly drain board core material with excellent biodegradability according to the present invention comprises a biodegradable composition having excellent flexibility and improved biodegradation rate due to controlled crystallinity, and the biodegradable composition preferably comprises plant-derived or petroleum-based 1,4-butanediol, succinic acid, bishydroxybutylene adipate-succinate-terephthalate oligomer, a catalyst, and a stabilizer, and it is more preferable to prepare the composition by mixing 100 parts by weight of plant-derived or petroleum-based 1,4-butanediol, 120 to 140 parts by weight of succinic acid, 12 to 18 parts by weight of bishydroxybutylene adipate-succinate-terephthalate oligomer, 0.1 to 0.2 parts by weight of catalyst, and 0.1 to 0.2 parts by weight of stabilizer, and then proceeding with an esterification reaction followed by a polycondensation reaction.

[0022] The above-mentioned bis-hydroxybutylene adipate-succinate-terephthalate (BHBAST) oligomer is prepared by mixing 35 to 45 parts by weight of succinic acid, 45 to 55 parts by weight of adipic acid, 80 to 90 parts by weight of dimethyl terephthalate, 0.05 to 0.1 parts by weight of tetrabutyl titanate, and 0.1 to 0.2 parts by weight of trimethyl phosphate with 100 parts by weight of 1,4-butanediol and carrying out an esterification reaction. The oligomer prepared through the above process exhibits a long chain form and has a weight-average molecular weight of 800 to 2000 g / mol. The oligomer exhibiting such a weight-average molecular weight has the effect of controlling crystallinity by disrupting the regular arrangement within the polybutylene succinate crystal structure.

[0023] At this time, when the above bishydroxybutylene adipate-succinate-terephthalate oligomer is contained in an amount of 12 to 18 parts by weight, it has appropriate crystallinity and exhibits the effect of improving excellent flexibility and biodegradation rate.

[0024] Through this, the biodegradable composition used in the present invention can effectively control the high crystallinity of polybutylene succinate and secure excellent mechanical properties by significantly improving elongation without reducing tensile strength. Furthermore, since plasticizers are not used, migration issues or problems with reduced long-term stability do not occur. Moreover, the components used in the biodegradable composition and oligomer synthesis can be replaced with biomass-derived raw materials, thereby increasing the biomass content of the final resin composition.

[0025] The byproduct (water or methanol) generated during the esterification reaction of the above oligomer is removed using a vacuum or inert gas atmosphere of the reactor, and the bishydroxybutylene adipate-succinate-terephthalate oligomer thus prepared has a sufficiently long molecular chain that interferes with the crystal structure of polybutylene succinate, while having high fluidity compared to the polymer resin, allowing it to participate smoothly in the reaction.

[0026] In the above biodegradable composition, the reaction catalyst may be a titanium-based catalyst, such as a titanium alkoxide like tetrabutoxytitanate (Ti(OBu)4) or titanium isopropoxide (Ti(OiPr)4), in an amount of 0.1 to 0.2 parts by weight. The titanium-based catalyst is widely used in polyester condensation polymerization and is known to be relatively safe in terms of toxicity issues, and the reaction temperature is about 190 to 230°C, and the vacuum is maintained in the range of about 0.1 to 1.5 Torr.

[0027] In the above biodegradable composition, a stabilizer may be used in an amount of 0.1 to 0.2 parts by weight, and examples thereof may include trimethyl phosphate, triethyl phosphate, tributyl phosphate, etc.

[0028] In the above biodegradable composition, the esterification reaction is carried out at a temperature of 200 to 220°C for 120 to 200 minutes. When the esterification reaction proceeds as described above, an efficient ester bond is formed between 1,4-butanediol and a dicarboxylic acid such as succinic acid, thereby sufficiently generating oligomers. Additionally, water, which is a reaction byproduct, is effectively removed, shifting the reaction equilibrium. This not only provides conditions for stably forming high molecular weight polyesters in the subsequent condensation step but also improves productivity by appropriately increasing the reaction rate while minimizing quality degradation caused by thermal decomposition or over-reaction.

[0029] At this time, if the esterification reaction proceeds at a temperature below 200°C or for less than 120 minutes, the formation of ester bonds between 1,4-butanediol and dicarboxylic acid is insufficient, resulting in insufficient oligomer formation and insufficient removal of water, which is a reaction byproduct, making it difficult to stably form high molecular weight polyester in the subsequent condensation step. Furthermore, if the esterification reaction is carried out at a temperature exceeding 220°C or for more than 200 minutes, thermal decomposition or over-reaction occurs, damaging the oligomer structure and potentially causing a change in color and a deterioration in the physical properties of the biodegradable composition, which is undesirable.

[0030] In addition, the polycondensation reaction in the above biodegradable composition is carried out for 150 to 200 minutes at a temperature of 240 to 250°C and a reduced pressure of 1.5 Torr or less. When the polycondensation reaction is carried out under the above conditions, the ester bonds formed in the oligomer stage are effectively continuously bonded to grow polymer chains, and low-molecular-weight substances (water, alcohol, etc.) that are reaction by-products are efficiently removed under reduced pressure, thereby not only stably forming high-molecular-weight polyester, but also securing mechanical strength and thermal stability by appropriately controlling the crystallinity of the resin simultaneously with the increase in molecular weight, and minimizing quality degradation caused by thermal decomposition or over-reaction.

[0031] At this time, if the above polycondensation reaction is carried out at less than 240°C or for less than 150 minutes, continuous bonding between oligomers is not sufficiently formed, resulting in incomplete formation of high molecular weight polyester and a low molecular weight of the resin, which leads to insufficient mechanical strength and thermal stability. If the above polycondensation reaction is carried out at more than 250°C or for more than 200 minutes, over-reaction and thermal decomposition occur, which damages the oligomer structure and may result in quality problems such as changes in resin color, deterioration of physical properties, and failure to control viscosity, which is undesirable.

[0032] When analyzed using differential scanning calorimetry (DSC), the drain board core material made of the biodegradable composition produced through the above process exhibits lower crystallinity compared to polybutylene succinate resin alone; this is because long-chain oligomers interfere with the regular crystallization process of polybutylene succinate.

[0033] In addition, results measured through tensile testing (based on ASTM D4595) confirmed that while the decrease in tensile strength of the drain board core material was not significant, the elongation increased significantly compared to polybutylene succinate alone.

[0034] Furthermore, measurements of the biodegradability of drain board core materials under industrial composting conditions revealed that the rate of biodegradation improves as the crystallinity of polybutylene succinate decreases. This is because a reduction in the crystalline region leads to an increase in the amorphous region, which facilitates the initiation of hydrolysis and consequently causes rapid initial degradation.

[0035] Meanwhile, the biodegradable composition used in the present invention can be synthesized using biomass-derived succinic acid, adipic acid, terephthalic acid, and 1,4-butanediol at the raw material stage for manufacturing oligomers and polybutylene succinate, thus exhibiting the advantage of being able to increase the biomass content of the final component.

[0036] Accordingly, the above-mentioned biodegradable composition can be effectively applied to the drain board core material according to the present invention, as it exhibits excellent flexibility and improved biodegradation rate due to controlled crystallinity compared to conventional polybutylene succinate.

[0037] Meanwhile, the biodegradable composition, which is composed of the above-mentioned components and has excellent flexibility and improved biodegradation rate due to controlled crystallinity, may further include additives such as calcium carbonate, thermoplastic resin, and lubricant in addition to the components described above. In this case, it is preferable to include 5 to 20 parts by weight of calcium carbonate, 1 to 10 parts by weight of thermoplastic resin, and 0.1 to 5 parts by weight of lubricant per 100 parts by weight of the biodegradable composition.

[0038] The calcium carbonate above acts as a filler to improve the mechanical properties of the biodegradable composition. If the content of the calcium carbonate is less than 5 parts by weight, defects occur due to the inherent shrinkage of the biodegradable composition, and the above effect is negligible. If the content of the calcium carbonate exceeds 20 parts by weight, the product may be cut during production, or the mechanical strength may be significantly reduced.

[0039] The above thermoplastic resin serves to improve the mechanical strength of the above biodegradable resin. If the content of the above thermoplastic resin is less than 1 weight part, the dispersion of calcium carbonate becomes irregular, and the strength of the molded product is formed inconsistently. If the amount of the above thermoplastic resin added exceeds 10 weight parts, the strength of the product may decrease due to poor mixing with the biodegradable composition.

[0040] At this time, the thermoplastic resin may be polypropylene or polyethylene, and in some cases, a mixture of polypropylene and polyethylene in an appropriate weight ratio may be used. For example, the mixture may be a mixture of polypropylene and polyethylene in a weight ratio of 1:9 to 9:1.

[0041] If the content of the above lubricant is less than 0.1 parts by weight, there is a disadvantage that productivity becomes poor due to insufficient lubrication, and if the amount of the above lubricant added exceeds 5 parts by weight, product defects may occur due to excessive lubrication.

[0042] At this time, the above lubricant acts to improve the flowability of the biodegradable composition and the dispersibility of each composition, improves the shrinkage of the final product, and increases mold release so that a product with a beautiful surface can be provided. Any lubricant for polymer compounds can be used without special limitation, but higher fatty acids are the most common. It is preferable to use one or more selected from the group consisting of oleic acid amide, ersylate amide, molybdenum disulfide, glycerol monostearate, palmityl alcohol, or silicone powder. It is even more preferable to use a mixture comprising 40 to 50 weight% of dimethyl silicone oil or a silane coupling agent mixed with low-density polyethylene having a weight-average molecular weight of 5,000 to 10,000.

[0044] The eco-friendly drain board with excellent biodegradability according to the present invention comprises a core material for an eco-friendly drain board with excellent biodegradability containing a biodegradable composition manufactured through the above process, and a filter material surrounding the core material, wherein the core material has a plurality of drainage channels formed therein, and the filter material is formed of a polylactic acid fiber material.

[0045] The drain board composed of the above components and structure is equipped with an eco-friendly drain board core material with excellent biodegradability and workability, and a filter material made of polylactic acid fiber with excellent biodegradability; as it naturally decomposes in the soil, it is not only eco-friendly but also exhibits excellent workability.

[0047] Hereinafter, the method for manufacturing an eco-friendly drain board core material with excellent biodegradability according to the present invention, the drain board core material manufactured through the method, and the physical properties of a drain board to which the drain board core material is applied will be explained with reference to examples.

[0049] <Preparation Example 1> Preparation of Bis-hydroxybutylene Adipate-Succinate-Terephthalate Oligomer

[0050] 135 g (1.5 mol) of 1,4-butanediol, 53 g (0.45 mol) of succinic acid, 65 g (0.45 mol) of adipic acid, 116 g (0.6 mol) of dimethyl terephthalate, 0.1 g of tetrabutyl titanate, and 0.2 g of trimethyl phosphate were added to a flask reactor (500 ml), and the esterification reaction was carried out for 120 minutes while stirring and gradually raising the temperature to 210°C, and a bishydroxybutylene adipate-succinate-terephthalate oligomer was prepared while confirming that the reaction with byproducts was no longer proceeding.

[0052] <Example 1>

[0053] 177 g (1.5 mol) of plant-derived succinic acid, 135 g (1.5 mol) of plant-derived 1,4-butanediol, 23.50 g (7 wt%) of bishydroxybutylene adipate-succinate-terephthalate oligomer prepared in Preparation Example 1, 0.1 g of tetrabutyl titanate and 0.1 g of dibutyltin oxide as catalysts, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml); the temperature was gradually raised to 210°C while stirring and the esterification reaction was carried out for 119 minutes; the temperature was then raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes; after the reaction was completed, a high vacuum environment was created stepwise over 40 minutes, and subsequently, a polycondensation reaction was carried out for 179 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr to produce a biodegradable having low crystallinity and improved flexibility. A drain board core material with multiple drainage channels was manufactured using an extruder and a core material molding device.

[0055] <Example 2>

[0056] 177 g (1.5 mol) of plant-derived succinic acid, 135 g (1.5 mol) of plant-derived 1,4-butanediol, 16.43 g (5 wt%) of bishydroxybutylene adipate-succinate-terephthalate oligomer prepared in Preparation Example 1, 0.1 g of tetrabutyl titanate and 0.1 g of dibutyltin oxide as catalysts, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml); the temperature was gradually raised to 210°C while stirring and the esterification reaction was carried out for 120 minutes; the temperature was then raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes; after the reaction was completed, a high vacuum environment was created stepwise over 40 minutes, and then a polycondensation reaction was carried out for 175 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr to produce a biodegradable having low crystallinity and improved flexibility. A drain board core material with multiple drainage channels was manufactured using an extruder and a core material molding device.

[0058] <Example 3>

[0059] The drain board core material produced through Example 1 above was formed to a thickness of 3.0 millimeters, and the drain board was manufactured by wrapping the formed drain board core material with a filter material (polylactic acid fiber material) with a thickness of 0.35 millimeters.

[0061] <Comparative Example 1>

[0062] 177 g (1.5 mol) of plant-derived succinic acid, 135 g (1.5 mol) of plant-derived 1,4-butanediol, 0.1 g of tetrabutyl titanate as a catalyst, 0.1 g of dibutyltin oxide, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml), and while stirring, the temperature was gradually raised to 210°C and the esterification reaction was carried out for 149 minutes. Then, the temperature was raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes. After the reaction was completed, a high vacuum environment was created stepwise for 40 minutes, and then a condensation polymerization reaction was carried out for 181 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr. The biodegradable composition prepared was then used to manufacture a drain board core material with multiple drainage channels through an extruder and a core material molding device.

[0064] <Comparative Example 2>

[0065] 177 g (1.5 mol) of petroleum-based succinic acid, 135 g (1.5 mol) of petroleum-based 1,4-butanediol, 0.1 g of tetrabutyl titanate as a catalyst, 0.1 g of dibutyltin oxide, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml), and while stirring, the temperature was gradually raised to 210°C and the esterification reaction was carried out for 128 minutes. Then, the temperature was raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes. After the reaction was finished, a high vacuum environment was created stepwise for 40 minutes, and then a condensation polymerization reaction was carried out for 176 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr. The petroleum-based biodegradable composition prepared was then used to manufacture a drain board core material with multiple drainage channels through an extruder and a core material molding device.

[0067] <Comparative Example 3>

[0068] 177 g (1.5 mol) of plant-derived succinic acid, 135 g (1.5 mol) of plant-derived 1,4-butanediol, 0.31 g (0.1 wt%) of bishydroxybutylene adipate-succinate-terephthalate oligomer prepared in Preparation Example 1, 0.1 g of tetrabutyl titanate and 0.1 g of dibutyltin oxide as catalysts, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml); the temperature was gradually raised to 210°C while stirring and the esterification reaction was carried out for 117 minutes; the temperature was raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes; after the reaction was completed, a high vacuum environment was created stepwise over 40 minutes, and then a polycondensation reaction was carried out for 173 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr to produce a biodegradable having low crystallinity and improved flexibility. A drain board core material with multiple drainage channels was manufactured using an extruder and a core material molding device.

[0070] <Comparative Example 4>

[0071] 177 g (1.5 mol) of plant-derived succinic acid, 135 g (1.5 mol) of plant-derived 1,4-butanediol, 3.15 g (1 wt%) of bishydroxybutylene adipate-succinate-terephthalate oligomer prepared in Preparation Example 1, 0.1 g of tetrabutyl titanate and 0.1 g of dibutyltin oxide as catalysts, and 0.2 g of trimethyl phosphate as a stabilizer were added to a flask reactor (500 ml); the temperature was gradually raised to 210°C while stirring and the esterification reaction was carried out for 120 minutes; the temperature was then raised to 245°C and the reaction was carried out under a nitrogen atmosphere for 10 minutes; after the reaction was completed, a high vacuum environment was created stepwise over 40 minutes, and then a polycondensation reaction was carried out for 180 minutes at a temperature of 245°C and a reduced pressure of 1.0 Torr to produce a biodegradable having low crystallinity and improved flexibility. A drain board core material with multiple drainage channels was manufactured using an extruder and a core material molding device.

[0073] <Experimental Example 1> Measurement of Physical Properties of Drain Board Core Material

[0074] The elongation, tensile strength, and melting enthalpy (△) of the drain board core material prepared through the above Examples 1 and 2 and Comparative Examples 1 to 4 m ) and crystallinity were measured and are shown in Table 1 below.

[0075] {However, the above tensile strength and elongation were measured using a universal testing machine based on ASTM D4595, and

[0076] The above enthalpy of fusion (△ m ) was measured using Differential Scanning Calorimetry (DSC) according to the ASTM D3418 test method, and

[0077] The crystallinity was measured using a DSC (Differential Scanning Calorimeter) under a nitrogen atmosphere by raising the temperature from -30°C to 200°C at a heating rate of 10°C per minute and then lowering it to -30°C. The degree of crystallinity was determined by calculating the heat of melting generated during this process using the theoretical enthalpy of crystallization (110.3 J / g) of polybutylene succinate.

[0078] division Elongation rate (%) Tensile strength (kN / full width) Enthalpy of fusion (J / g) Crystallinity (%) Example 1 28 2.02 30.9 28.01 Example 2 25 2.11 36.3 32.91 Comparative Example 1 19 2.28 60.2 54.58 Comparative Example 2 20 2.31 60.1 54.49 Comparative Example 3 18 2.30 59.2 53.67 Comparative Example 4 21 2.27 57.5 52.13

[0079] As shown in Table 1 above, it was found that the drain board core material produced through Examples 1 to 2 of the present invention showed an increased elongation compared to the drain board core material produced through Comparative Examples 1 to 4, but a minimal decrease in tensile strength, and exhibited excellent biodegradability with low melting enthalpy and crystallinity.

[0081] <Experimental Example 2> Measurement of Biodegradability of Drain Board Core Material

[0082] The biodegradability of the drain board core materials prepared through Examples 1 and 2 and Comparative Examples 1 to 4 was measured and is shown in Table 2.

[0083] The biodegradability of the drain board core material was measured using the ISO 14855 method (measurement of aerobic biodegradability of plastic materials under composting conditions) at 58 ± 2 ℃ and a moisture content of 50 ± 5 %.

[0084] division 30 days 60 days 90 days Example 1 75% 91% 98% Example 2 70% 88% 97% Comparative Example 1 52% 72% 93% Comparative Example 2 54% 73% 91% Comparative Example 3 56% 78% 94% Comparative Example 4 58% 80% 95%

[0085] As can be seen in Table 2 above, the drain board core materials of Examples 1 and 2 had superior biodegradability compared to Comparative Examples 1 to 4.

[0087] <Experimental Example 3> Measurement of physical properties of drain board core material and drain board to which the same is applied

[0088] The physical properties of the drain board core material of Example 3 above and the filter material (polylactic acid fiber material) of the drain board to which it is applied were commissioned to the FITI Testing & Research Institute to measure tensile strength, drainage performance, vertical permeability coefficient, and effective pore size. As a result, the physical properties of the drain board core material are shown in Table 3 below, and the physical properties of the filter material are shown in Table 4 below.

[0089] Measurement items Measurement method Measurements tensile strength KS K ISO 10319 : 2015 3.19 kN / width Drainage performance 1) KS K 0940 : 2018 80.0 cm 3 / S

[0090] 1) Pressurization pressure: 300 kPa, Hydraulic gradient: 0.5, Pressurization time: 1 week

[0091] Measurement items Measurement method Measurements tensile strength KS K ISO 10319 : 2015 Machine direction: 5.86 kN / m Width direction: 2.93 kN / m Vertical permeability coefficient 1) KS K ISO 11058 : 2029, static head method 1.3 X 10 -2 cm / s Effective hole size 2) KS K ISO 12956 : 2019 44 μm

[0092] 1) Head loss: 50 mm, Basis for calculating vertical permeability coefficient: ASTM D4491 / D4491M-222)

[0093] 2) Exposed sample area: 177 cm² 2

[0095] As shown in Tables 3 and 4 above, the drain board core material and filter material produced through Example 3 of the present invention had excellent physical properties such as mechanical properties, drainage performance, and vertical permeability coefficient.

[0097] Accordingly, the eco-friendly drain board core material with excellent biodegradability according to the present invention and the drain board to which the core material is applied provide an eco-friendly drain board core material with excellent processability and biodegradability and a drain board to which the core material is applied, by applying a biodegradable composition that includes a long-chain structured oligomer with a weight-average molecular weight of 800 to 2000 g / mol to control the crystallinity of polybutylene succinate, thereby exhibiting excellent flexibility and improved biodegradation rate.

Claims

Claim 1 The composition comprises a biodegradable composition having excellent flexibility and improved biodegradation rate due to controlled crystallinity, wherein the biodegradable composition is prepared by mixing 100 parts by weight of plant-derived or petroleum-based 1,4-butanediol, 120 to 140 parts by weight of succinic acid, 12 to 18 parts by weight of bishydroxybutylene adipate-succinate-terephthalate oligomer, 0.1 to 0.2 parts by weight of catalyst, and 0.1 to 0.2 parts by weight of stabilizer, carrying out an esterification reaction, and then carrying out a polycondensation reaction, wherein the bishydroxybutylene adipate-succinate-terephthalate oligomer comprises 35 to 45 parts by weight of succinic acid, 45 to 55 parts by weight of adipic acid, 80 to 90 parts by weight of dimethyl terephthalate, and 0.05 to tetrabutyl titanate in 100 parts by weight of 1,4-butanediol. An eco-friendly drain board core material with excellent biodegradability, characterized by being prepared by mixing 0.1 parts by weight of and 0.1 to 0.2 parts by weight of trimethylphosphate and carrying out an esterification reaction. Claim 2 delete Claim 3 delete Claim 4 An eco-friendly drain board core material with excellent biodegradability, characterized in that, in claim 1, the catalyst comprises tetrabutyl titanate and dibutyltin oxide in a weight ratio of 1:

1. Claim 5 An eco-friendly drain board core material with excellent biodegradability, characterized in that, in claim 1, the stabilizer comprises trimethylphosphate. Claim 6 An eco-friendly drain board core material with excellent biodegradability, characterized in that, in claim 1, the esterification reaction is carried out at a temperature of 200 to 220°C for 120 to 200 minutes. Claim 7 An eco-friendly drain board core material with excellent biodegradability, characterized in that, in claim 1, the condensation reaction is carried out for 150 to 200 minutes at a temperature of 240 to 250°C and a reduced pressure of 1.5 Torr or less. Claim 8 An eco-friendly drain board having excellent biodegradability, comprising: a core material for an eco-friendly drain board having excellent biodegradability according to any one of claims 1 or claims 4 to 7; and a filter material surrounding the core material, wherein the core material has a plurality of moisture passages formed therein and the filter material is formed of a polylactic acid fiber material.

Citation Information

Patent Citations

  • Biodegradable polyester resin and articles containing it

    JP2016520706A

  • Copolyester resin composition and a process ofpreparation thereof

    KR1020010055721A

  • Biodegradable drain board

    WO2021204918A1